Color alteration in teeth subjected to different bleaching techniques - Briso, André Luiz Fraga [UNESP]; Fonseca, M. S. M. [UNESP]; Almeida, L. C. A. G. de [UNESP]; Mauro, Silvio José [UNESP]; Santos, Paulo Henrique dos [UNESP] (Maik Nauka/interperiodica/springer, 2010)
This study evaluated the color alteration of teeth subjected to the action of different bleaching agents and the influence of light sources commonly used in association with these products, In GI, the specimens remained immersed in artificial saliva. The specimens in GII were bleached with a 10% carbamide peroxide gel 4 hours/day during 3 weeks; the teeth in the other three groups were subjected to three sessions of three 10-min applications of 35% hydrogen peroxide gel at 7-day intervals. In GIII, no light was used, while in GIV and GV the gel was associated with a quartz-tungsten-halogen light and a LED/laser source, respectively. The teeth color was evaluated before and 7 days after the bleaching sessions by reflectance spectrophotometry. Data were analyzed statistically by ANOVA and Fisher's test (alpha = 0.05), and showed that a significant color change was obtained in all treated groups. After the first week of treatment and at the end of it, the bleaching protocols showed similar results. The results of the present study indicate that association of a light source is not necessary to obtain the bleaching effect and that optimal bleaching can be achieved with all techniques tested.